Special Issue: Surface Modification of Magnesium, Aluminum Alloys, and Steel - Titu, Aurel Mihail; Miao, Bin; Pop, Alina Bianca (Coatings (Basel), 2022)
[...]the mechanisms leading to the decomposition and degradation of organic coating systems are described and types of adhesion loss are discussed. The thickness has a great influence on the performance of the coating. [...]the technique used to find the thickness is of great importance for coating research and technology. [8] described the most suitable method for finding the thickness of metal coatings. [...]technologies are divided into two categories: destructive and non-destructive. [...]future research on HEA films and coatings is recommended.